Antiviral drugs (non-HIV) - Shaw, Megan (Henry Stewart Talks, 2018)
Why do we need antiviral drugs?, Overview of approved antiviral drugs, Antiviral targets mechanisms and resistance, Hepatitis C virus: biology and current drugs, Hepatitis B virus: biology and treatments, Herpesvirus drugs, Influenza virus: approved drugs, Broad-spectrum antivirals, Diseases for which we need antivirals